Community Based Early Childhood Education Management - Kadar Kadar; Rochmat Wahab; Siti Fatonah (ISTAWA, 2020)
This study aims to find theories about community-based Kindergarten educational institutions management. Data were collected objectively, not influenced by observers' wishes, using questionnaires, interviews, observation sheets, and interview guides. Data validation used data triangulation method between researchers, practitioners, namely the headmasters, teachers, school committees, parents of students, and community leaders involved in Kindergarten in Kebumen Regency. Pragmatically, this study found a theory about the functions and implementation of Kindergarten that are managed professionally with support and community participation. The organization of Kindergarten educational institution organizers carried out based on the job description, the meaning is between schools, communities, and parents have their roles, functions and responsibilities based on a joint decision with increasing the growth and development of Kindergarten (Raudhlatul Athfal) professionally and competitive. Educational institution development program of Kindergarten starts with the community's idea, carried out by teacher under community supervision, and the community evaluates the results. The community functions as the facilitator of building's physical development program, completeness of facilities and other infrastructure as well as the quality development program for Kindergarten educational institution professionally.Penelitian ini bertujuan untuk menemukan teori tentang manajemen lembaga pendidikan TK berbasis masyarakat. Data dikumpulkan secara obyektif, tidak dipengaruhi oleh keinginan pengamat, menggunakan kuesioner, wawancara, lembar observasi, dan panduan wawancara. Validasi data menggunakan metode triangulasi data antara peneliti, praktisi, yaitu kepala sekolah, guru, komite sekolah, orang tua siswa, dan tokoh masyarakat yang terlibat di Taman Kanak-kanak di Kabupaten Kebumen. Secara pragmatis, penelitian ini menemukan teori tentang fungsi dan implementasi TK yang dikelola secara profesional dengan dukungan dan partisipasi masyarakat. Organisasi penyelenggara lembaga pendidikan TK dilaksanakan berdasarkan uraian tugas, artinya antara sekolah, masyarakat, dan orang tua memiliki peran, fungsi dan tanggung jawab mereka sendiri berdasarkan keputusan bersama dengan meningkatkan pertumbuhan dan perkembangan Taman Kanak-Kanak (Raudhlatul Athfal) secara profesional dan kompetitif . Program pengembangan lembaga pendidikan TK dimulai dengan gagasan masyarakat, dilaksanakan oleh guru di bawah pengawasan masyarakat, dan hasilnya dievaluasi oleh masyarakat. Komunitas ini berfungsi sebagai fasilitator program pembangunan fisik bangunan, kelengkapan fasilitas dan infrastruktur lainnya, serta program pengembangan kualitas untuk lembaga pendidikan TK secara profesional.